Effects of Different Intervertebral Space Heights on Nerve Root Tension during Posterior Lumbar Interbody Fusion. Issue 4 (27th February 2023) - Wu, Yujie; Zhu, Tong; Fu, Zhiyi
Abstract : Objective: There is no effective standard method to evaluate whether the nerve root tension is restored during lumbar decompression surgery, which is an important indicator for the recovery of nerve function. This study aimed to investigate the feasibility of intraoperative nerve root tension measurement and to confirm the correlation between nerve root tension and intervertebral space height. Methods: A total of 54 consecutive patients (mean age, 54.3 years; range, 25–68 years) received posterior lumbar interbody fusion (PLIF) for lumbar disc herniation (LDH) with lumbar spinal stenosis and instability. The 110%, 120%, 130%, 140% height values of each lesion were calculated based on preoperative measurements of the intervertebral space height. The heights were intraoperatively expanded after the intervertebral disc was removed using the interbody fusion cage model. The tension value of nerve root was measured by pulling the nerve root for 5 mm with a self‐made measuring device. The nerve root tension value was measured before decompression, after discectomy at 100%, 110%, 120%, 130%, and 140% of the height of each intervertebral space, and after placement of the cage during intraoperative nerve root tension monitoring. Results: The nerve root tension values at 100%, 110%, 120%, and 130% heights were significantly lower than those before decompression, and there was no statistical significance among the four groups. The nerve root tension value was significantly higher at 140% height and was statistically significant compared with that of 130% height. The nerve root tension value after cage placement was significantly lower than that before decompression (1.32 ± 0.22 N vs . 0.61 ± 0.17 N, p  < 0.01), and the postoperative VAS score was also significantly improved (7.0 ± 2.24 vs . 0.8 ± 0.84, p  < 0.01). The nerve root tension was positively correlated with the VAS score (F = 85.19, p  < 0.01; F = 78.65, p  < 0.01). Conclusion: This study demonstrates that nerve root tonometry can perform instant noninvasive intraoperative nerve root tension measurement. There is a correlation between nerve root tension value and VAS score. We found that when the height of the intervertebral space was increased to 140% of the original height, the nerve root tension increased the risk of injury significantly. Abstract : Nerve root tonometry can perform instant noninvasive intraoperative nerve root tension measurement.